Loss revives bistable state near the exceptional point in a non-Hermitian microwave photonic meta-molecule - Kejia Zhu; Yong Sun; Jie Ren; Hong Chen (New Journal of Physics, 2017)
By exploring the extraordinary property of exceptional points (EPs) in non-Hermitian systems, we here demonstrate that losses can play a constructive role in controlling bistable states. We experimentally realize the EP in a non-Hermitian meta-molecule of coupled resonators in a microwave regime. By increasing the loss, we first observe the bistable state suppression at the weak-dissipative regime, and then the bistable state recovery in the strong-dissipative regime. Both the experimental and theoretical analysis demonstrate that the revival of bistable states results from the revival of the field intensity after the system encounters EPs, in spite of the increasing loss. Our results provide an alternative way to controlling and manifesting bistable systems so as to achieve flexible photonic devices not limited to the microwave regime.